DISEÑO DE UN PICOSATÉLITE PARA EL MONITOREO Y PREDICCIÓN DEL COMPORTAMIENTO DE INCENDIOS FORESTALES - Miguel Felipe Cano Bogotá; Valeria Navarro Lizcano; Ricardo Andrés Santa Quintero (Revista Ingeniería, Matemáticas y Ciencias de la Información)
Currently, high temperatures, the burning of waste or waste disposal in forested areas and even the use of fire for therenewal of vegetation in agriculture have increasingly increased the occurrence of forest fires, so this research proposesthe study of different environmental factors through a decentralized network of CANSATS, because through the monitoringand analysis of the different environmental factors in real time can be favored to make decisions in situations ofmaterialization of the risk of forest fires.